P136 Sexual health services have a key role in the diagnosis and initial assessment of hepatitis C. (23rd May 2012) - Donson, H; Rogstad, K E; Campbell, L; Raza, M; Cope, A
Abstract : Background: Hepatitis C is a major cause of liver disease, cirrhosis and liver cancer but is increasingly amenable to treatment. Sexual health services often have unique access to test patients within risk groups. Aim: To assess the role of sexual health services in diagnosis and initial assessment of Hepatitis C (HCV). Method: Patients diagnosed with HCV at a large inner city sexual health service from 1 July 2009 to 30 June 2011 were identified along with a control group of negative patients. Results: 4430 HCV tests were performed on 3395 patients. 53 (1.56%) were HCV antibody positive of which 26 (49%) were PCR positive with a detectable viral load. Where genotyping was performed the majority were 3A (50%), 1A (22%) or 1B (22%). The most common reasons for testing were intravenous drug use (64%), men who have sex with men (15%) and sexual intercourse with a known IVDU (9%). 27 patients were referred to HCV services of which only 18 (67%) attended. The main reasons documented for testing within the control group were related to the patient's country of origin (32%), country of origin of a sexual partner (24%) or for men who have sex with men (19%). 34 countries were given as potential sources of increased risk, however only nine patients or sexual partners of patients originated from the three countries of highest HCV prevalence. Conclusion: Sexual health services provide a unique opportunity for HCV screening in those who may otherwise not be tested. Standardisation is required to clarify who constitutes high risk particularly related to country of origin of patient or sexual partner. Initial assessment of patients diagnosed with HCV in genitourinary medicine clinics may lead to more efficient and cost effective patient care.